ABOUT MATHEMATICAL DESIGN OF HEAT EXCHAGE PROCESSES IN STATIONARY LAYERS OF FRIABLE MATERIALS - Mnykh, Anton; Pazyuk, Mikhail; Ovchynnykova, Iryna; ВaryshenkoElen; Minyajlo, Nataliya (Scientific Journal "Metallurgy", 2022)
The questions of mathematical design of thermophysical properties of layer of friable material are considered, which would allow taking into account and representing basic properties of agglomerative process The methods of association are offered in the model of pictures of particle of friable material as thermally thin and thermally massive body. Influence of parameters of homogeneous mono- and polydisperse layer is investigated on its coefficient of heat conductivity. The estimation of influence of the system of loading and forming of layer is also conducted on distribution of material on a largeness and thermophysical properties as local horizons and all layer on the whole. On the basis of experimental data conformities to law of change of by volume coefficient of heat transfer in the layers of friable materials are set. Mathematical description of the considered processes is presented, the initial and border conditions of application of model are certain. The got model well describes thermophysical processes in layers without internal energy sources and in layers at incineration of hard fuel.